Synergistic anticancer activity of antimicrobial peptide nisin and doxorubicin against breast cancer cells via modulation of membrane permeability - Chanita Phetdee; Suwatjanee Naephrai; Malinee Pradain; Yanisa Panporm; Ubaid Ahmad; Panchika Prangkio (PLoS ONE, 2026)
Breast cancer is the most frequently diagnosed cancer and remains the leading cause of death among females. Despite the rapid advancement in cancer therapy, the development of more effective therapeutic strategies and anticancer agents with a new mode of action remains a critical challenge. Combination of therapeutic agents is an attractive approach to enhance drug efficacy. Nisin, a cationic antimicrobial peptide, has been reported for its cytotoxicity against some cancer cell lines via several mechanisms, particularly membrane disruption. Nisin can bind preferentially to the negatively charged phospholipids, causing pore formation in cell membranes. In this study, we demonstrated that nisin exhibited membrane permeabilization preferentially with anionic lipids using liposomal leakage assay. Moreover, anticancer activity of nisin and doxorubicin (DOX) was investigated against two breast cancer cell lines, MCF-7 and MDA-MB-231, using MTT assay. Nisin demonstrated cytotoxic effect against breast cancer MCF-7 and MDA-MB-231, with IC 50 values of 5–8 µM, while exhibiting lower cytotoxicity toward normal cells. Based on Bliss independence analysis, the synergistic effect between nisin and DOX was markedly observed in MCF-7 when treated with 10 μM nisin and 1 μM DOX for 24–48 h treatment. Furthermore, as demonstrated by fluorescent-based high-content analysis, nisin clearly caused cell membrane permeability and promoted DOX-induced DNA damage in both cell lines. Flow cytometry with Annexin-V staining revealed that co-treatment of nisin and DOX significantly enhanced apoptosis, as compared to individual treatments, particularly in MCF-7 cells, suggesting a key mechanism of action for anticancer activity. Cationic nisin can interact with biological membrane and modulate membrane permeability and fluidity, consequently facilitating DOX entry, inducing apoptosis and DNA damage. Overall, this study demonstrates that the combination of nisin and DOX could offer a new therapeutic approach for breast cancer treatment with a reduced chemotherapeutic drug dosage.